Estô dalam Masyarakat Madura: Peran Kiai dan Blater dalam Mempertahankan Solidaritas Sosial di Era Modern - Listiana, Heni; Nurhayati, Sri; Qathrun Nada, Zilfania (Research Institute and Community Engagement of UIN MADURA, 2024)
Estô is a deeply rooted social tradition in Madurese society, reflecting values of selfless devotion, respect, and solidarity between individuals. This study aims to examine how the practice of estô is applied in Madurese society, particularly in relation to Kiai and the Blater community, and how it contributes to strengthening social bonds and maintaining harmony in the face of modernization challenges. The research employed a qualitative approach, using in-depth interviews and participatory observation in several villages on Madura Island. The findings show that while the practice of estô remains relevant, factors such as individualism, the influence of technology, and social change have impacted its execution. The community tends to prefer more practical forms of assistance, such as digital money transfers, over direct involvement in social activities. However, the core values of estô-solidarity, devotion, and mutual respect-remain intact despite changes in its form. This study concludes that although the methods of implementing estô have evolved, the essence and fundamental principles of the practice remain relevant and adaptable to modern times, preserving social solidarity in Madurese society. The preservation and strengthening of estô’s values are crucial for maintaining cultural identity and fostering harmonious social relationships in the future.